Henry's Constants Prediction Study of VOC in Several Types Solvents by UNIFAC-FV - Hendriyana (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2010)
Absorption of hydrophobic volatile organic compounds (VOC) such as toluene, was studied. In order to characterise the absorption capacity of toluene/oil solvent systems, the Henry's constant (H) was determined. Prediction of Henry's constants are also carried out using UNIFAC-FV model which is known to be suitable for hydrocarbon gases and high-boiling point hydrocarbon solvent.kg/cm2, 220 kg/cm2 dan 260 kg/cm2.